Uganda Protectorate Government Records - Uganda Protectortate Government
Includes ministry of education,ministry of health,Rent board, Ugand cotton association, Lint marketing board, development committee, Tariff appeals committee, standing committee on finance, compasation committe e, survey, land and mines department, co-operative societies,Uganda com pany, personalities: Sir Gerald Portal, J.J Willis, Wilson G.E.M, Westo n Jossio. L, manuscripts: The History of Buganda and its Kings, journal of Lango expedition by A.Z Bagelamu etc
AR/UG.PR
English, Luganda, Runyankore etc
Shelf no.1